Pengembangan Filsafat Ilmu Dalam Revitalisasi Pendidikan Politik di Indonesia - St. Ika Noerwulan Fraja; Fendi Setyawan; M. Arief Amrullah; Fitriyah Fitriyah; Moh. Wakid (Jurnal Ilmiah Global Education, 2026)
The development of the philosophy of science plays a strategic role in reconstructing the paradigm of political education in Indonesia, which has long tended to be formalistic and ceremonial. Ideally, political education serves as a space for cultivating citizens’ critical awareness. Through the perspective of epistemology, knowledge is understood as non-neutral and inherently linked to social interests and power relations. This study employs a qualitative method using a library research approach by examining the works of Jurgen Habermas, Paulo Freire, and relevant literature on the philosophy of science and political education in Indonesia. The analysis is conducted using a descriptive–reflective technique to explore the relationship between the development of the philosophy of science and the revitalization of political education. The findings show that critical epistemology requires a paradigmatic shift from a positivistic model of political education toward a dialogical and participatory model. Political education should not merely convey political facts but encourage citizens to understand the reasons and values underlying political structures. This paradigm positions political education as an emancipatory process that forms critical, rational, and empowered citizens. Thus, the development of the philosophy of science through critical epistemology serves as an essential foundation for constructing a more reflective, dialogical, and liberating political education, ultimately strengthening democratic quality in Indonesia.